Knowledge of Oral and Physical Manifestations of Anorexia Nervosa Among Polish Dentists: A Cross-Sectional Study - Krukowska-Zaorska, Agnieszka; Kot, Katarzyna; Marek, Ewa; Dura, Włodzimierz; Safranow, Krzysztof; Lipski, Mariusz (Frontiers in Psychiatry, 2021)
Background: Anorexia nervosa is a psychosomatic disorder and is commonly associated with impaired oral health. Dentists can play a relevant role in the early diagnosis of anorexia nervosa. With the help of intra- and extraoral examinations and anamnesis, the dentist can detect characteristic signs and symptoms of this eating disorder. The purpose of this study was to determine the knowledge regarding the oral and physical manifestations of anorexia nervosa among general dental practitioners and specialist dentists of Poland. Material and methods: A pretested online questionnaire consisting of a first part asking for the characteristics of the participant and a second part with 22 specific questions on their general knowledge of anorexia nervosa and knowledge of physical and oral manifestations of this eating disorder was used. Results: A total of 369 dentists completed the questionnaire. The Polish dentists in this study reported sufficient knowledge regarding anorexia nervosa. However, younger dentists and general dental practitioners had relatively lower knowledge scores than other groups. The dentists mainly had difficulties with the oral symptoms of anorexia nervosa. Conclusion: Despite Polish dentists having sufficient knowledge about anorexia nervosa in relation to the general symptoms of anorexia, there are deficits with regard to oral manifestations. Therefore, there is a need to increase continuing education in this field, which can improve early diagnosis of this disease by dental practitioners and referral to specialists for treatment.